Abordagem de especificação de requisitos baseada em projeto axiomático - Pereira, Ana Maria (2011)
This dissertation presents an approach that applies the Axiomatic Design Theory to the specification of software systems requirements. This Approach intends to improve the quality of design solution since its inception, which involves from the problem analysis to the requirements identification. The purpose of the proposed approach is to offer methods that allow the use of axiomatic design in a process of requirements engineering. The proposed requirements specification approach establishes the application of the Axiom of Independence in the study of problems and costumer needs. In this way, new domains, the problem domain and the costumer domain, are included in the requirements engineering process. It is established a hierarchical model for the decomposition of Problems, Needs and Requirements. A zig-zag process is suggested in order to use the propose approach in conjunction with a development process as the Unified Process. It is presented a case study of a system for equipment testing in a production line. The case study aims to demonstrate the practical application of the requirements specification approach proposed in this dissertation. In addition, the results of the experiments performed during the research are presented. The requirements specification process for a reporting system is shown to illustrate the experiments. This example helps billustrate how the proposed approach can be used to increase the consistency and quality of software requirements.